Attitudes to, and experience of, pooled sampling for sexually transmitted infection testing: a web-based survey of English sexual health services. (May 2018) - Shaw, Jonathan; Saunders, John Michael; Hughes, Gwenda
Chlamydia trachomatis and Neisseria gonorrhoeae testing guidance recommends extragenital screening with locally validated nucleic acid amplification tests, with anatomical sites tested separately. Evidence supports multi-patient combined aliquot pooled sampling (PS) for population screening; evidence for within-patient PS is sparse. Within-patient PS could be more cost-effective for triple-site testing, but requires distinct clinical pathways and consideration over loss of information to guide risk assessments and treatment. We explored PS attitudes and practices amongst clinicians in England. A cross-sectional web-based survey was distributed to clinical leads of sexual health services throughout England in February 2016. Fifty-two (52/216, 23%) services responded. One service reported current within-patient PS and two were awaiting implementation. Of the 49 services not pooling, five were considering implementation. Concerns raised included the inability to distinguish infection site(s) (36/52, 69%), absence of national guidance (34/52, 65%) and reduced assay performance (18/52, 34%). Only 8/52 (15%) considered the current level of evidence sufficient to support PS, with 40/52 (77%) requesting further validation studies and 39/52 (77%) national guidance. PS was rarely used by respondents to this survey, although the response rate was low. The clinical challenges presented by PS need to be addressed through further development of the evidence base.